PENERAPAN MODEL PEMBELAJARAN EVERYONE IS A TEACHER UNTUK MENGGALI POTENSI DIRI DAN MENINGKATKAN KETERAMPILAN SISWA KELAS V UPTD SD NEGERI 122384 JL. KOL PEMATANGSIANTAR PADA PEMBELAJARAN BAHASA INDONESIA MATERI CERPEN - Simanjuntak, Melvin; Jojor Parisma Simangunsong; Cristya Febrina Purba; Elfryani Sinaga; Putri Artha Ulina; Selfrina Sipayung; Fransisko Timoti Siallagan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to reveal the effectiveness of implementing the Everyone is a Teacher learning model in exploring personal potential and improving the skills of class V students in learning Indonesian at UPTD SD Negeri 122384 Pematangsiantar. The Everyone is a Teacher learning model was chosen because it gives every student the opportunity to act as a teacher, so it is hoped that it can improve students' skills, self-confidence and communication abilities. This research uses the classroom action research (PTK) method with two cycles. Data collection is carried out through observation and tests. With teaching materials in the form of a short story with the title There are butterflies, there are guests with the synopsis that the character "I" and his wife are sitting on the terrace, suddenly three butterflies pass by, come, go, and come again. Thinking that there will be guests coming. Is the guest who will come a good person or someone who brings bad luck? They thought that the guest would bring good luck, then went into the kitchen to prepare a banquet for the guests they were waiting for. Suddenly he saw an ugly butterfly, he had a bad feeling and suspected that what was coming was an unlucky guest. They started to be busy with bad thoughts about the guests who would come. The research results show that the application of the Everyone is a Teacher learning model significantly increases student activity in the learning process, understanding of concepts, and student learning outcomes in Indonesian language subjects. Apart from that, students also show improvements in self-confidence and communication skills. Based on the results of this research, it is concluded that the Everyone is a Teacher learning model is an effective learning model to be applied in Indonesian language learning in elementary schools.